The comparison of conformal radiotherapy with intensity – modulated radiotherapy for post-operative adjuvant radiation for patients with pancreas carcinoma - Idasiak, Adam; Wolny, Edyta; Wydmański, Jerzy; Hawrylewicz, Leszek; Miszczyk, Leszek (Contemporary Oncology/Współczesna Onkologia, 2004)
The aim of the article is to compare conformal radiotherapy (CFRT) with intensity-modulated radiotherapy (IMRT) in planning radical radiotherapy in patients with pancreas carcinoma. A treatment planning study was performed to compare CFRT with IMRT for eleven patients with pancreas carcinoma after Whipple operation. For everyone from this group two treatment plans with CFRT and IMRT were prepared. The CFRT plans consisted of two lateral and two oblique fields (4F) and the IMRT plans consisted of five fields (5F), two lateral and three oblique ones with orientations equal to the CFRT plans. Treatment plans were compared using dose-volume histograms. The ranges and median of the maximum, mean, and dose received by 50% of the PTV and critical organs were compared using nonparametric Mann-Whitney U test. The 5F IMRT plan provided a comparable PTV maximum, minimum and median dose and homogeneity with the CFRT plan. Median maximum doses were reduced in the IMRT plans for two of critical structures: liver (45.32 Gy – CFRT vs. 43.35Gy – IMRT; p=0.002) and the right kidney (25.7 Gy – CFRT vs. 19.55 Gy – IMRT; p=0.002). When comparing IMRT with CFRT in this group of patients with pancreas carcinoma no essential clinical differences were demonstrated in DVH in PTV and critical structures. IMRT is not recommended in routine radiotherapy planning as it is time-consuming.